Sound and identity explored through the Indian Tamil diaspora and Tamil Nadu. Issue 1 (2nd January 2017) - Devadoss, Christabel
ABSTRACT: Sound is very much a part of identity. While identities are neither singular nor stable, they can be expressed through sound in daily life. Scholars have used soundscapes in geography to understand urban environments within cities, rural national park systems, and provide musical insights into cultural landscapes. However, furthering discussion on the role of sound in identity can move concepts of soundscape and cultural landscape forward. The goal of this paper is to investigate how identity and culture, though they are dynamic, can be performed and stabilized through sound in particular moments and yet also exist banally. Soundscapes through both spoken language and music can give geographers further insights on identity and place. Sound can also show how non-dominant identities distinguish themselves from larger national identities. With research in Tamil Nadu, India and Cleveland, OH, this paper examines sound's role in identity, belonging, and community through lived experience and performance. Focusing on intersections and tensions between soundscapes, this paper investigates how the Tamil soundscape is used to assert and perform identity.